Repeated and long-term cryopreservation of primary bovine myogenic cells to maintain quality in biomimetic cultured meat - Kakehi, Roka; Yoshida, Azumi; Takahashi, Hironobu; Shimizu, Tatsuya (Frontiers in Sustainable Food Systems, 2023)
Cultured meat produced using cell culture technology can potentially alleviate many of the ethical, environmental, and public health concerns associated with conventional livestock meat production. The industrialization of cultured meat for wide-spread adoption requires new methods to efficiently collect high-quality cells and to preserve their cell quality. Cryopreservation is a widely used technique to enable the long-term storage of cells without causing severe damage. In this study, we focused on the feasibility of cryopreservation to maintain cell quality for storage of bovine myogenic cells harvested from bovine meat based on our unique primary culture method. Primary bovine cells were incubated in a culture dish and then cryopreserved at -80℃ for 1 week or 1 year. After thawing, the cells were further cultured for several passages to evaluate the abilities of the cells to proliferate or differentiate into myotubes. Furthermore, the cells were repeatedly cryopreserved for 1 week each time to investigate the impact of the repeated freezing and thawing. Consequently, long-term (within 1 year) or repeated (up to 3 times for 1 week each) cryopreservation at -80℃ caused no degradation in the abilities of the cells to proliferate or differentiate, which is important for cultured meat production. We also confirmed that the cryopreservation did not require any unique cell freezing media. Moreover, based on our tissue engineering technique, our cryopreserved bovine myogenic cells had the ability to form sarcomere structures and produce muscle contractions even after they were frozen for 1 year. Although the bovine muscle tissues described here require more mature structures and functions in order to closely mimic native muscle tissue, we believe that the functional maturation of myogenic cells is essential to produce a “tissue-engineered meat” that will have native-like nutrients, texture, and taste that consumers will expect in the future. These results reveal the potential of cryopreserving quality-controlled bovine myogenic cells to contribute to a stable supply of high-quality cells for cultured meat production.